Optimized one-way electric vehicle carsharing system in campus environment using heterogeneous non-dominated sorting genetic algorithm II - Abdulazeez, Omar Saud (2019)
The general public are attracted to the carsharing systems based on the cost associated with the system and its efficiency in terms of service delivery. The accessibility and proximity of vehicle stations to its customers influence the service delivery; that is, the customer’s travel distance between origin and destination from the vehicle stations and the availability of vehicles at stations when the need arises determine the efficiency of the system. Conversely, the fleet size, station number and availability of vehicles at the designated locations at the right time determines carsharing system establishment and operation costs.